Analisis Faktor Penyebab Terjadinya Benturan KM Dharma Rucitra VII dengan Dermaga Wae Kelambu saat Olah Gerak Sandar - Bramanta Asadhika Bagaskara; Hadi Setiawan; Nurul Fadliana (Jurnal Multidisiplin Indonesia, 2026)
Maritime transportation plays a vital role in trade, distribution of goods, and inter-regional and inter-island connectivity, ensuring that shipping safety remains a priority. One of the high-risk stages is the ship's maneuvering during berthing, as this phase generates significant momentum due to the influence of internal and eksternal forces. This study aims to analyze the factors causing the collision between the KM Dharma Rucitra VII and Wae Kelambu Pier during berthing and to identify preventive measures to prevent similar incidents from recurring. Furthermore, this study emphasizes the importance of compliance with the Regulation of the Minister of Transportation of the Republic of Indonesia Number 57 of 2015 concerning the use of tugboats and pilotage vessels. The study was conducted on the KM Dharma Rucitra VII owned by PT Dharma Lautan Utama from August 2024 to August 2025 using a qualitative descriptive method. Data were obtained through interviews and written and oral reports. The focus of the study included the factors causing the collision and preventive measures. The results showed that the collision was influenced by both internal and eksternal factors. Fixed internal factors include the ship's technical limitations, particularly the use of a single screw propulsion system and the utilization of a bow thruster. Internal factors that are not fixed are related to human resources, such as suboptimal anticipation and coordination between the captain and crew during the berthing process. Meanwhile, eksternal factors such as sudden weather changes, such as heavy rain, strong winds, reduced visibility, and ocean currents, also affect the stability and control of the ship. Preventive measures are carried out through improving crew competency, careful maneuver planning that takes into account weather conditions and the water environment, and a thorough evaluation of each berthing process to minimize the risk of similar incidents in the future.